Macronutrient Intake at Student Breakfast at SD Negeri 76 Manado, Indonesia - Elfredo Josua Halawa; Olfie Sahelangi; Ruqayah Junus; Meildy Esthevanus Pascoal; Siti Nurhasanah; Nonce Legi; Romiza Arika (Archives of The Medicine and Case Reports, 2023)
Breakfast is food eaten before or near the start of daily activities, no less than two hours after waking up, usually no later than 10.00 and increases calorie intake by around 20-35% of the body's daily needs. Macronutrients are chemical bonds designed for the body to carry out its functions, namely producing energy, building and maintaining tissue, and regulating life processes. Macronutrients include carbohydrates or energy, fat, and protein. This type of research is quantitative descriptive, which was carried out using a cross-sectional method. The sample in this study was class 4 and class 5, totaling 60 people. Data collection was obtained from the results of breakfast recall interviews using a recall form. The results of the study showed that the majority of school children's protein intake category was 43 people (71.7%) poor and 17 people (28.3%) good. For the fat intake category, school children were grouped at less than 56 people (93.3%) and good at 4 people (6.7%), and the dominant carbohydrate intake category is less than 60 people (100%). Of all the results of the intake categories for children in grades 4 and 5 at SD Negeri 76 Manado, the intake of micronutrients in the morning intake was deficient, namely carbohydrate intake, which was 100%, with the number of students being 60 people.